HPLC Fingerprint Analysis Combined with Chemometrics for Authentication of Kaempferia galanga from Related Species - Cahya Septyanti; Irmanida Batubara; Mohamad Rafi (Universitas Gadjah Mada, 2016)
Fingerprint analysis using high performance liquid chromatography (HPLC) has been developed for authentication of Kaempferia galanga from related species, such as Kaempferia pandurata and K. rotunda. By comparing the fingerprint chromatograms of K. galanga, K. pandurata and K. rotunda, we could identify K. galanga samples and detect adulteration of K. galanga from K. pandurata and K. rotunda by using their marker peaks. We also combined HPLC fingerprint with chemometrics for discrimination the three species and also for authentication of K. galanga. All the three species and K. galanga adulterated with K. pandurata and K. rotunda were discriminated successfully by using principal component analysis (PCA) and discriminant analysis (DA). This result indicates that HPLC fingerprint analysis in combination with PCA (PC1 = 30.06% and PC2 = 34.74%) and DA (DF1 = 94.59% and DF2 = 3.32%) could be used for authentication of K. galanga samples from the related species.